PERAN KEBUTUHAN PSIKOLOGIS DALAM MENINGKATKAN PRESTASI AKADEMIK SISWA SDN KARTINI 5 - Nurkholis; Wulan Nurhidayah; Khaylila Najwa Afifah; Khaerunnisa; Naela Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Needs are everything that is required to live a prosperous life. When people are able to fulfill their needs, they will prosper. One aspect that is equally important is psychological needs, especially for students, which play a major role in supporting their social, academic and emotional development. This research is to find out what are the roles of psychological needs in improving students' academic achievement. The descriptive qualitative method was chosen because it provides an opportunity to describe phenomena that occur in the field with a focus on in-depth understanding, through comprehensive observations and interviews. So the results of the research through interviews conducted with 6 students from SD Negeri Kartini 5 can be found in several aspects ranging from preferred lessons, how students learn, activities that students do when they are lazy to learn, and students' academic motivation, it is found that by maintaining mental health, students can avoid feeling depressed, losing enthusiasm, and a sense of alienation in the social environment. Therefore, the fulfillment of learners' psychological needs greatly affects their academic success, social relationships, and emotional well-being. The environment around them, including support from loved ones, plays a significant role in creating an atmosphere conducive to such growth.